2020
DOI: 10.1111/ejn.14854
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interaction between striatal cholinergic and low‐threshold spiking interneurons — A computational study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Consistent with previous studies, we found that optogenetic stimulation of CINs evoke a long pause in the firing activity of LTSIs that is mediated mostly by mAChRs activation and a participation of GABA A receptors certainly via CIN-activation of THINs 5,6,14,53,54 . Here, in addition to confirming these data, we also show the presence of an EPSC/P in most recorded LTSIs that involve both nAChRs and glutamate receptor activation.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we found that optogenetic stimulation of CINs evoke a long pause in the firing activity of LTSIs that is mediated mostly by mAChRs activation and a participation of GABA A receptors certainly via CIN-activation of THINs 5,6,14,53,54 . Here, in addition to confirming these data, we also show the presence of an EPSC/P in most recorded LTSIs that involve both nAChRs and glutamate receptor activation.…”
Section: Discussionsupporting
confidence: 92%
“…37 By virtue of their unique reward-associated modulation, 2 LTSIs are ideally situated to control the timing and magnitude of dopamine signals during learning. In addition to directly gating striatal dopamine, LTSIs further participate in this local modulatory microenvironment through strong inhibitory control over ChINs, [38][39][40][41] which also directly and strongly regulate striatal dopamine. [8][9][10][11][12] As both LTSIs and ChINs are dynamically modulated by discrete components of reward learning and performance, future work should delineate how these interneurons work in concert to shape dopamine signals during ongoing goal-directed behavior.…”
Section: Reportmentioning
confidence: 99%
“…In another study from the same research team, the authors used computational modelling to examine the reciprocal interactions between striatal cholinergic interneurons and low-threshold spiking (LTS) interneurons. They show that their modelled connections capture the experimental evidence for physiological interactions between the two neuronal populations, and mimic findings on the muscarinic (M4) and nitric oxide modulation of LTS and cholinergic interneurons respectively (Frost Nylen et al, 2020). The next two articles focus on the function of the parvalbumin-containing, fastspiking, striatal GABAergic interneurons.…”
Section: E D I T O R I a L Special Issue Editorial: Basal Ganglia/movement Disordersmentioning
confidence: 65%